Italy : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2007)
This Report on the Observance of Standards and Codes (ROSC) data module provides an assessment of Italy's macroeconomic statistics against the Special Data Dissemination Standard (SDDS) complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The report covers the national accounts, the consumer price index (CPI), the producer price index (PPI), and the government finance statistics (GFS). The report reveals that in comparison with the situation in 2002, Istat has the primary responsibility for the dissemination of general government statistics to the public.